2021
DOI: 10.1108/ijm-04-2021-0222
|View full text |Cite
|
Sign up to set email alerts
|

The labour market impact of COVID-19: early evidence for a sample of enterprises from Southern Europe

Abstract: PurposeThe choice of Southern Europe is partly based on the observation that the sample includes a number of countries whose economies faced more severe difficulties than elsewhere in Europe. Economically they were less able to absorb the economic shock posed by COVID-19. It is also partly based on the characteristics of the pandemic. A number of countries in the sample were amongst the earliest in Europe to be hit by the pandemic and a several were harder hit in terms of both morbidity and mortality.Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Hence, we found evidence that the COVID-19 crisis has increased the odds of getting fired of permanent workers by more than the ones of temporary workers. This is consistent with the finding of Webster et al (2021a) that, after the emergence of the COVID-19 crisis, there is a relatively low proportion of Portuguese firms firing temporary workers when compared to other countries or to permanent workers. It may be explained by the temporary workers' higher flexibility, particularly with respect to schedule and location (Spurk and Straub, 2020), which makes them more able to adapt to this new and disruptive context.…”
Section: Covid-19 Impact On Job Losses In Portugalsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, we found evidence that the COVID-19 crisis has increased the odds of getting fired of permanent workers by more than the ones of temporary workers. This is consistent with the finding of Webster et al (2021a) that, after the emergence of the COVID-19 crisis, there is a relatively low proportion of Portuguese firms firing temporary workers when compared to other countries or to permanent workers. It may be explained by the temporary workers' higher flexibility, particularly with respect to schedule and location (Spurk and Straub, 2020), which makes them more able to adapt to this new and disruptive context.…”
Section: Covid-19 Impact On Job Losses In Portugalsupporting
confidence: 92%
“…As occupations with low WFH feasibility and lower skill levels are typically associated with lower wages, the COVID-19 crisis seems to be contributing to increase socioeconomic inequalities. Considering our results and that, according to Webster et al (2021a), Portuguese firms face extended difficulties in implementing remote working when compared to other Southern European firms, it is thus important, in the current scenario, to invest in the digital transformation of organizations and in the training of the workforce accordingly, thus improving WFH feasibility. This process must be a joint effort by public authorities (such as the IEFP), businesses and workers and must be accompanied by an adequate reinforcement in the physical capital and technology.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Small firms were in particular heavily affected due to their financial fragility and limited access to commercial financing (Bartik et al, 2020). A host of studies document the negative impact on small firms in terms of revenue loss, production and employment, business closures, layoffs, liquidity, and gender inequality (see, e.g., Dai et al, 2020;Apedo-Amah et al, 2020;Bartik et al, 2020;Humphries et al, 2020;Adams-Prassl et al, 2020;Borland and Charlton, 2020;Fairlie, 2020a,b;Cirera et al, 2021;Bachas et al, 2021;Webster et al, 2021;Khamis et al, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, there is no study on firm survival in developing economies during the COVID-19 pandemic. Using an inverse probability matching analysis, Webster et al (2021) found that government supports are less effective than loans for firm survival in 6 European countries. Note that, during COVID-19, European countries are more effective than developing economies.…”
Section: Literature Review Hypothesis Development and Datasetmentioning
confidence: 99%